Does the triceps-on approach affect alignment in total elbow arthroplasty? A cadaveric study. (October 2019) - King, Andrew; Evans, Jonathan P; Booker, Simon J; Beazley, James CS; Jones, Robin JS; Thomas, William JC; Smith, Christopher
Background: The triceps-on approach for total elbow arthroplasty has gained popularity due to the theoretical benefit of preserving the extensor mechanism. However, there is concern that the exposure may be reduced in comparison to a triceps-off approach and may affect the implant alignment achieved. Method: Total elbow arthroplasties were implanted in 18 randomised, paired cadaveric elbows using the triceps-on or triceps-off approach. The bones were dissected out and the position of the implants measured relative to anatomical landmarks. The flexion/extension and varus/valgus angles, and the distance of centre of rotation from the anatomic centre of rotation in the sagittal plane for both components were obtained as well as the humeral component rotation relative to the transepicondylar axis. Results: All humeral components were positioned in external rotation and all ulna components were placed in flexion. Seven components were positioned greater than 5° away from the ideal in one measurement, with no significant difference between the two approach groups. Discussion: This unique study showed no significant difference in the alignment of the implants between the two approaches. These results support the theory that the triceps-on approach does not result in larger alignment errors in component positioning when performing total elbow arthroplasty.